Gearshift performance improvement for an electromagnetic gearshift system based on optimized active disturbance rejection control method. (February 2019) - Lin, Shusen; Li, Bo; Jiao, Weidong
Electric automated manual transmission usually adopts direct current motors and intermediate gearings to accomplish gear change. The structure can be simplified further to achieve better dynamic response and mechanical efficiency. A new type of gearshift system which adopts two electromagnetic linear actuators is presented. The intermediate gearings including motion converters are canceled, and the electromagnetic linear actuators drive the shift fork directly to move the synchronizer to engage different gears. The novel gearshift system is described in detail, including the connection, working principle, and performance. Specific working phases of the synchronization are introduced and mathematical equations of each phase are provided. After the specific feature analysis of each phase, the performance effect factors are deduced and the corresponding control requirements are proposed. Considering the stability of the performance, the robust control method, namely, active disturbance rejection control, is adopted. The time optimal method is introduced to optimize the dynamic response of the active disturbance rejection control method to achieve a shorter gearshift time. Comparative simulations among the active disturbance rejection control, time optimal–active disturbance rejection control, and proportional–integral–derivative methods show the distinct improvements of the novel gearshift system combined with the time optimal–active disturbance rejection control method. Finally, gearshift experiments are implemented. The results demonstrated the availability of the novel gearshift system and the designed control strategy.